International law and domestic legal systems incorporation, transformation and persuasion - Shelton, Dinah (Oxford : Oxford University Press, 2011)
By providing a systematic analysis of how international law is incorporated and implemented in over two dozen states, this text analyzes how the international order and national legal systems interact with each other.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International and municipal law; Comparative law